Pengembangan Sumber Daya Manusia Melalui Pendidikan Non Formal dan In Formal di Kabupaten Tuban - M Thoyyib (Al Hikmah: Jurnal Studi Keislaman, 2021)
In development, humans are planners, actors, controllers and the goal of development itself. Therefore, the development of the quality of human resources is a top priority that must be improved, so that they can have all the capabilities needed in development in all fields. Quality human beings can take advantage of all their potential and be able to seize future opportunities for the glory of the nation and state. The human factor is the most decisive for the success or failure of a nation to remain upright in global competition because what distinguishes the ability of a nation from other nations is its human quality. The central point that is the key to the success or failure of a nation in building its country, depends on the quality of its human resources. The author argues, Islam, especially in Indonesia, can emerge with strong and quality Muslims if it has three factors that have been fulfilled, namely "faith, knowledge, and good deeds" or productive actions which are indicators of the high and low quality of human resources. Humans who have steadfast faith, high and useful knowledge and productive work are superior human resources that must be realized in the future. The complexity of education issues on the one hand and the demands to improve the quality of human resources on the other hand cause educational issues to remain interesting to discuss with the hope that this discussion will be able to bring up alternative solutions in developing the quality of human resources through non-formal and informal education. Keywords: Non-Formal Education, Education Science, Tuban Regency